How important are general equilibrium models for small open economies – a case of Croatia - Škare, Marinko; Stjepanović, Saša (Technological and Economic Development of Economy, 2013)
This paper develops a general equilibrium model for the Republic of Croatia to evaluate CGE model use in macroeconomic management and forecasting. Since Croatia is a small open country subject to large external shock and growth constraints efficient macroeconomic management framework is fundamental. The lack of data prevents to follow historic economic variables over a longer period of time, which is why CGE models look as possible solution. CGE models use calibration to solve the problem of missing most macroeconomic variables. After developing the model, we use it to run different scenarios for economic policies using a CGE model for Croatia. Results show that CGE model can be an important instrument for policy makers in running macroeconomic policies for small open countries.